Analisis Kinerja Keuangan Menggunkan Laporan Arus pada PT Cahaya Bintang Medan Tbk (2020-2022) - Syahril; Almadany , Khairunnisa; Prasetya , Linda (Cattleya Darmaya Fortuna, 2024)
It is very necessary to assess financial performance to find out the extent of a company's achievements or success in the activities it has carried out. A cash flow report is needed in a company to reveal a company's ability to generate cash for an accounting period. The purpose of conducting this research is to determine cash flow ratio analysis in assessing the financial performance of a company. This research uses the cash flow ratio. The cash flow ratios used are the operating cash flow ratio, the cash to interest coverage ratio, the cash to current debt coverage ratio and the total debt ratio. The type of data used is external data obtained through the official website www.idx.co.id PT. Cahaya Bintang Medan Tbk, which is the 2020-2022 financial report. The results of the research show that PT. Cahaya Bintang Medan Tbk, has poor financial performance when viewed from the operating cash ratio because the debt value is greater than the operating cash flow value so that the company has not been able to pay its current liabilities, as well as when viewed from the cash coverage ratio. to current debt and total debt ratio, but in 2022 the cash flow to interest ratio is considered quite good because the company is able to cover interest costs of 74 , thus the author tries to conclude that the performance of PT.Cahaya Bintang Medan Tbk is not good because the amount of liabilities is greater rather than the value of operating cash flows.